2015
DOI: 10.1007/s11069-014-1569-6
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of soil erosion in some sections of Lower Jinsha River based on RUSLE

Abstract: Soil erosion increasingly poses a great threat to human food security and environmental quality. It is necessary to implement the assessment of soil erosion so as to provide precautionary measures and relevant suggestions for soil conservation. In this paper, the soil erosion model, revised universal soil loss equation (RUSLE), was used to quantify the soil loss in a large mountainous area of Lower Jinsha River Basin. The analysis of the datasets by means of geographic information systems (GIS) together with R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(28 citation statements)
references
References 39 publications
2
24
0
2
Order By: Relevance
“…The correlation analysis of erosion rate with slope and elevation in the study area revealed that the interrelationship between erosion and slope was very significant (r = 0.72, P \ 0.001). The present results also incorporated the previous study by Jiang et al (2015).…”
Section: Resultssupporting
confidence: 84%
See 3 more Smart Citations
“…The correlation analysis of erosion rate with slope and elevation in the study area revealed that the interrelationship between erosion and slope was very significant (r = 0.72, P \ 0.001). The present results also incorporated the previous study by Jiang et al (2015).…”
Section: Resultssupporting
confidence: 84%
“…On the other hand, dense forests play an important role in soil conservation. Therefore, the afforestation program in this region is essential and should be implemented strictly (Sharma 2010;Bhunia and Shit 2013;Jiang et al 2015). The calculated R factor for the study area is shown in Table 4.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Otras investigaciones de Lee (2004); Kheir et al (2006); Vrieling (2006) Vergari (2015); Jiang et al (2015); Aucelli et al (2016) aplican, retoman, y proponen otras metodologías para el estudio y mapeo de la erosión. Yang y Zhu (2003) explican que para el estudio de la erosión se usan actualmente los sensores remotos y los Sistemas de Información Geográfica (GIS) y que se dividen en la interpretación visual, análisis espectrales, determinación de parámetros, así como la interpretación interactiva con criterios de experto y de computadora.…”
Section: Introductionunclassified